Molecular basis of vitamin E action: tocotrienol modulates 12-lipoxygenase, a key mediator of glutamate-induced neurodegeneration - Khanna, Savita; Roy, Sashwati; Ryu, Hoon; Bahadduri, Praveen; Swaan, Peter W; Ratan, Rajiv R; Sen, Chandan K (The Journal of biological chemistry, 2003)
Vitamin E is a generic term for tocopherols and tocotrienols. This work is based on our striking evidence that, in neuronal cells, nanomolar concentrations of alpha-tocotrienol, but not alpha-tocopherol, block glutamate-induced death by suppressing early activation of c-Src kinase (Sen, C. K., Khanna, S., Roy, S., and Packer, L. (2000) J. Biol. Chem. 275, 13049-13055). This study on HT4 and immature primary cortical neurons suggests a central role of 12-lipoxygenase (12-LOX) in executing glutamate-induced neurodegeneration. BL15, an inhibitor of 12-LOX, prevented glutamate-induced neurotoxicity. Moreover, neurons isolated from 12-LOX-deficient mice were observed to be resistant to glutamate-induced death. In the presence of nanomolar alpha-tocotrienol, neurons were resistant to glutamate-, homocysteine-, and l-buthionine sulfoximine-induced toxicity. Long-term time-lapse imaging studies revealed that neurons and their axo-dendritic network are fairly motile under standard culture conditions. Such motility was arrested in response to glutamate challenge. Tocotrienol-treated primary neurons maintained healthy growth and motility even in the presence of excess glutamate. The study of 12-LOX activity and metabolism revealed that this key mediator of glutamate-induced neurodegeneration is subject to control by the nutrient alpha-tocotrienol. In silico docking studies indicated that alpha-tocotrienol may hinder the access of arachidonic acid to the catalytic site of 12-LOX by binding to the opening of a solvent cavity close to the active site. These findings lend further support to alpha-tocotrienol as a potent neuroprotective form of vitamin E.